2016
DOI: 10.1259/bjr.20150624
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of blood flow in paediatric brain tumours—a comparative study of dynamic susceptibility contrast and multi time-point arterial spin labelled MRI

Abstract: Objective:Arterial spin-labelling (ASL) MRI uses intrinsic blood water to quantify the cerebral blood flow (CBF), removing the need for the injection of a gadolinium-based contrast agent used for conventional perfusion imaging such as dynamic susceptibility contrast (DSC). Owing to the non-invasive nature of the technique, ASL is an attractive option for use in paediatric patients. This work compared DSC and multi-timepoint ASL measures of CBF in paediatric brain tumours.Methods:Patients (n = 23; 20 low-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Eight studies including 286 patients were included in the meta-analysis. 17,[27][28][29][30][31][32][33] The study selection is presented in the On-line Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies including 286 patients were included in the meta-analysis. 17,[27][28][29][30][31][32][33] The study selection is presented in the On-line Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…17,[27][28][29]32,33 Two studies used pulsed ASL. 30,31 Four of 8 studies used 1.5T, with the remaining using 3T. Risk of bias within studies as assessed by the QUADAS-2 tool, which showed a general low or indeterminate risk of bias (Fig 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors of the central nervous system are the most common group of solid tumors in children and account for 20% to 25% of childhood neoplasms [1] [2] [3]. In the United States, mortality rates among children with brain tumors exceed those in children with acute lymphoblastic leukemia [1]. Magnetic Radiologic Imaging (MRI) is the required non-invasive investigation for the diagnosis of brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…There are different types with variable survival rates depending on the histology, biology, age, and degree of spread. Some types of brain tumors may be completely resected, many cannot be removed without a considerable degree of morbidity [1].…”
Section: Introductionmentioning
confidence: 99%